2017
DOI: 10.1016/j.appdev.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Spanish instruction in head start and dual language learners' academic achievement

Abstract: Data from the Head Start Impact Study (N = 1,141) and the Head Start Family and Child Experiences Survey, 2009 Cohort (N = 825) were used to investigate whether Spanish instruction in Head Start differentially increased Spanish-speaking Dual Language Learners’ (DLLs) academic achievement. Although hypothesized that Spanish instruction would be beneficial for DLLs’ early literacy and math skills, results from residualized growth models showed there were no such positive associations. Somewhat surprisingly, DLL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Four studies (18%) explored TEH by Head Start center characteristics. Miller (2017) and Walters (2015) considered center characteristics separately, such as teacher's education level, student/staff ratio, and the curriculum, while Lee (2019) used a composite measure for the center quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies (18%) explored TEH by Head Start center characteristics. Miller (2017) and Walters (2015) considered center characteristics separately, such as teacher's education level, student/staff ratio, and the curriculum, while Lee (2019) used a composite measure for the center quality.…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, among children with non-parental care at baseline, the beneficial effect on the frequency of parental book reading for the child was larger for children with higher baseline cognitive skills ( Lee & Lee, 2016 ). For Spanish-speaking dual language learners, multiple studies found larger beneficial effects of Head Start on various cognitive outcomes ( Bitler et al, 2014 ; Bloom & Weiland, 2015 ; Feller et al, 2016 ; Miller, 2017 ). Cooper and Lanza (2014) also found that latent class subgroups with dual language learners had larger beneficial effects on both cognitive and social-emotional outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Many schools offer English as a second language (ESL) classes; however, they fail to provide accommodations for the students throughout each class and teachers are often not qualified to provide adequate instruction to these students within their classroom (Calderon et al, 2011). Head Start children who did not speak English at home had more positive benefits when the instruction was provided in Spanish (Miller, 2017). Overall, schools need to provide early and ongoing ESL supports across the student’s entire curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a part of the achievement gap may be attributed to assessing DLLs in either their native or nonnative language alone, not both. Researchers frequently assess the mathematics performance of Spanish-speaking DLLs in Spanish (Landry et al, 2019), in English (Choi et al, 2018), or separate Spanish and English measures (Foster et al, 2019; Méndez et al, 2019; Miller, 2017), but not a composite measure that simultaneously takes Spanish and English knowledge into account. Given varying language and mathematics performance among Spanish-speaking DLLs (e.g., J.…”
Section: Numeracy Differencesmentioning
confidence: 99%